Inovasi Teknologi Bioproses Melalui Pembelajaran Proses Fermentasi Susu menjadi Minuman Yogurt Probiotik - Dian Kharismadewi; Sri Wardhani; Rusdiana; Jenny Marshanda Valencia; Putri Angelina; Husnul Khotimah; Efiza Kurniasari (Institut Pertanian Bogor, 2026)
Science education is essential to the high school level learning curriculum, particularly Biology Lessons. Every student's learning must develop critical, analytical, innovative, and creative thinking skills by implementing both theoretical and practical approaches. In Biology Education subject, there is learning about bioprocess that involves the use of microbes (bacteria). Community service activities are conducted to illustrate the application of bioprocess technology in the fermentation of milk into probiotic yoghurt drinks and to serve as learning materials that enrich students’ knowledge of the fermentation process. Diversification of milk sources and methods using wet and dry lactic acid bacteria is introduced to students to enhance their knowledge and enrich learning materials related to biological technology innovation concepts. Community service activities are carried out in the form of pre-tests, material presentations, practices, organoleptic tests, post-tests, and filling out questionnaires on the level of student understanding and satisfaction. From the results of the post-test, an increase in the level of student understanding of making yoghurt was obtained by 87%. The results of the organoleptic test showed that all yoghurt products prepared met the SNI 2981: 2009 quality standards for the yoghurt condition test criteria, including texture, odour, taste, and consistency, except for yoghurt from almond milk. The preference level of students for yoghurt reached 96% for yoghurt made from cow's milk with strawberry flavour. This activity positively affects students by enhancing their science skills and knowledge while offering an opportunity to integrate yoghurt product innovation into school entrepreneurship. And so, this program is expected to become the basis for developing biotechnology learning in schools and improving community nutrition.